Optimizing the scanning window size for the distance measuring from digital images - Kozlov, Vladimir L. (Journal of the Belarusian State University. Physics, 2019)
The solution of the increasing accuracy task of restoring a three-dimensional space picture based on two-dimensional digital images requires the use of new effective techniques and algorithms for processing and analyzing digital images. The technique for automatically setting the scanning window sizes for digital range measurement is developed, which consists in calculating the discrete image gradients of an object using contrast boundary detection filters and then forming the scanning window size based on the analysis of contrast transitions. This increases the measurement reliability and accelerates the processing of the image contrast areas. An analysis of the determining accuracy of the correlation function extremum position in the subpixel range for techniques based on the center-of-mass, parabolic, and Gaussian algorithms is carried out. The technique for accuracy increasing of the extremum position determining is developed. The technique ensures measurement uncertainty in hundredths of a pixel.